Cross-validation of segments of credit card holders - Martins, M.C.; Cardoso, M. G. M. S. (Journal of Retailing and Consumer Services, 2012)
This work presents the segmentation of credit cards holders of a Portuguese financial institution. It is focused on the evaluation of the obtained solution via cross-validation. The proposed approach specifically handles a large data set with mixed (numerical and categorical) variables. It provides the evaluation of the internal stability of the segmentation solution and helps in characterizing the segments. Furthermore, it provides classification rules for new credit card holders. Finally, this work presents the credit card holders' segment profiles, helping to support ongoing and future strategic decisions.